F1. Is there a correlation between total body water distribution and haemodynamic changes during pregnancy?. (12th August 2016) - Pisani, I.; Lo Presti, D.; Tiralongo, G. M.; Gagliardi, G.; Farsetti, D.; Vasapollo, B.; Novelli, G. P.; Andreoli, A.; Valensise, H.
Abstract: Introduction : During pregnancy, maternal body composition and haemodynamics undergo important changes that are of increasing interest for understanding the evolving maternal physiology. Targets : To assess and correlate changes in body composition and haemodynamic function of healthy normotensive pregnant women. To identify different populations based on TVR values, we enrolled 235 patients subjected to bioimpedance analysis and haemodynamic assessment using the USCOM system. Results : We found an increase of BMI as result of an increase of all its components and a change in water distribution: ECW percentage increases while ICW decreases (see table). With regard to haemodynamics, we observed an increase in CO, SV and HR during all trimesters and a decrease in TVR. We divided the patients into two groups according to TVR values: we found lower TBW in patients with high TVR during the second trimester of pregnancy (see figure). Conclusions : Assessment of BMI is unable to disentangle the components of weight gain. TBW is strictly related to plasma volume expansion and has an important role in cardiac function enhancement. Assessment of TBW and TVR may identify patients with different adaptation to pregnancy: women with high TVR and insufficient plasma volume expansion and women with high TVR and excessive fluid retention.